A qualitative exploration into the experience of mindfulness in moderate-severe persistent depression - Timothy Sweeney; Elena Nixon; Richard Morriss; Patrick Callaghan (PLoS ONE, 2025)
Depression is a common and growing mental health problem, with around 5% of the world’s population experiencing an episode of depression during their lifetime. Relapse rates are high, with around half experiencing more than one depressive episode and a further 10–20% experiencing a chronic and persistent depression. Mindfulness has been incorporated into treatments for depression and several studies have explored the impact of mindfulness training on depressive symptomatology and recurrence. However, to date no studies have looked at the changing relationship between mindfulness and depression in those naïve to mindfulness training. 20 participants with moderate-to-severe persistent depression were interviewed to explore their experience of mindfulness in the context of low mood. Thematic analysis captured six themes highlighting changes in mindfulness relating to the onset of depression. Themes included: behavioural withdrawal; perceptual detachment from one’s experience; intentional reduction in awareness; increased self-criticism; mind racing; impaired cognitive performance. Thematic analysis suggested that mindfulness reduces in the context of moderate-to-severe persistent depression. This appears to occur indirectly as the consequence of depression-related processes, e.g., rumination and experiential avoidance, but also arises as a deliberately instigated self-protective strategy. However, findings seemed to indicate that reduced mindfulness maintains and intensifies depressive experience. Despite growing evidence of the value of mindfulness approaches for those with more chronic and severe depression, study findings suggest that introducing mindfulness to this population may be particularly challenging due to the intensity of symptomatology potentially obstructing access to a mindful perspective. Findings bear important implications for the treatment of depression and can inform future intervention development and delivery.